2019
DOI: 10.1371/journal.pone.0215475
|View full text |Cite
|
Sign up to set email alerts
|

What is the effect of a Mediterranean compared with a Fast Food meal on the exercise induced adipokine changes? A randomized cross-over clinical trial

Abstract: Background Adipose tissue-derived adipokines are pro-inflammatory cytokines involved in metabolic-related diseases and can be influenced by diet and exercise. We aimed to compare the effect of a Mediterranean (MdM) compared with Fast Food (FFM) meal on the exercise induced adipokines changes. Methods In a double blinded cross over trial, 46 participants were randomly assigned to one of two standardized iso-energy pre-exercise meals: FFM or MdM-type. Three hours after ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Mice lacking adipsin exhibit worsened glucose homeostasis in states of metabolic stress caused by diet-induced obesity and previous reports demonstrate the dysregulation of adipsin in models of obesity and diabetes [ 50 , 51 ]. In the present study, participants who achieved a greater MDS, presented with higher adipsin, which is consistent with the single previous study in this area [ 52 ], where adipsin was increased in response to both exercise and a MedDiet intervention in adults with no underlying medical conditions. In contrast, fast foods with high saturated or total fat content have been shown to reduce adipsin concentrations [ 52 , 53 ], establishing adipsin as a potentially important link between diet and obesity/energy homeostasis, systemic metabolism and immunoregulation.…”
Section: Discussionsupporting
confidence: 92%
“…Mice lacking adipsin exhibit worsened glucose homeostasis in states of metabolic stress caused by diet-induced obesity and previous reports demonstrate the dysregulation of adipsin in models of obesity and diabetes [ 50 , 51 ]. In the present study, participants who achieved a greater MDS, presented with higher adipsin, which is consistent with the single previous study in this area [ 52 ], where adipsin was increased in response to both exercise and a MedDiet intervention in adults with no underlying medical conditions. In contrast, fast foods with high saturated or total fat content have been shown to reduce adipsin concentrations [ 52 , 53 ], establishing adipsin as a potentially important link between diet and obesity/energy homeostasis, systemic metabolism and immunoregulation.…”
Section: Discussionsupporting
confidence: 92%
“…The authors suggested that fast food meals may cause dysfunction of adipokines, increasing insulin secretion and, consequently, the activity of the SNS. 49 Importantly, there is evidence showing that a dysfunction in the ANS may be implicated in the pathogenesis of obesity. 9 Guarino et al 9 reported a connection between the ANS and the GI system that keeps a balanced energy homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a series of experiments show that astrocytes in the hippocampus interact with microglia by secreting LCN2 in the rodent brains [ 66 ]. According to previous studies, physical exercise upregulates ORM level [ 103 , 104 ] and LCN2 [ 105 , 106 ]. Improving neuroplasticity and behaviors are found in lipocalin 2-null mice after exercise [ 107 ]; these findings note a potential effect of exercise on neuroplasticity by ORM2 or LCN2 from the astrocyte-microglia interaction ( Fig.…”
Section: Molecular Pathways Underlying Exercise-induced Astrocyte Crosstalkmentioning
confidence: 99%